JAK/STAT inhibition augments soleus muscle function in a rat model of critical illness myopathy via regulation of complement C3/3R. (2nd May 2021) - Addinsall, Alex B.; Cacciani, Nicola; Akkad, Hazem; Salah, Heba; Tchkonia, Tamara; Kirkland, James L.; Larsson, Lars
Abstract : Key points: Critical illness myopathy (CIM) is a frequently observed negative consequence of modern critical care. Chronic Janus kinase (JAK)/signal transducer and activator of transcription activation impairs muscle size and function and is prominent following mechanical ventilation. We identify pSTAT‐3 activation in tibialis anterior of CIM patients, before examining the potential benefits of JAK1/2 inhibition in an experimental model of CIM, where muscle mass and function are impaired. CIM activates complement cascade and increased monocyte infiltration in the soleus muscle, which was ameliorated by JAK1/2 inhibition, leading to reduced muscle degeneration and improved muscle force. Here, we demonstrate that JAK1/2 inhibition augments CIM muscle function through regulation of the complement cascade. Abstract: Critical illness myopathy (CIM) is frequently observed in response to modern critical care with negative consequences for patient quality of life, morbidity, mortality and healthcare costs. Janus kinase (JAK)/signal transducer and activator of transcription (STAT) activation is observed in limb muscles following controlled mechanical ventilation. Chronic JAK/STAT activation promotes loss of muscle mass and function. Thus, we hypothesized that JAK1/2 inhibition would improve muscle outcomes for CIM. Following 12 days of intensive care unit conditions, pSTAT‐3 levels increased in tibialis anterior muscle of CIM patients ( P = 0.0489). The potential of JAK1/2 inhibition was assessed in an experimental model of CIM, where soleus muscle size and force are impaired. JAK1/2 inhibition restores soleus force ( P < 0.0001). CIM activated muscle complement cascade, which was ameliorated by JAK1/2 inhibition ( P < 0.05, respectively). Soleus macrophage number corresponded with complement activity, leading to reduced muscle degeneration and augmented muscle function ( P < 0.05). Thus, JAK/STAT inhibition improves soleus function by modulating the complement cascade and muscle monocyte infiltration. Collectively, we demonstrate that JAK/STAT inhibition augments muscle function in CIM. Key points: Critical illness myopathy (CIM) is a frequently observed negative consequence of modern critical care. Chronic Janus kinase (JAK)/signal transducer and activator of transcription activation impairs muscle size and function and is prominent following mechanical ventilation. We identify pSTAT‐3 activation in tibialis anterior of CIM patients, before examining the potential benefits of JAK1/2 inhibition in an experimental model of CIM, where muscle mass and function are impaired. CIM activates complement cascade and increased monocyte infiltration in the soleus muscle, which was ameliorated by JAK1/2 inhibition, leading to reduced muscle degeneration and improved muscle force. Here, we demonstrate that JAK1/2 inhibition augments CIM muscle function through regulation of the complement cascade.